Velocity coefficient of tangential supply of subsonic centripetal turbine - A. A. Kishkin; A. V. Delkov; Yu. N. Shevchenko; M. U. Abdullaev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Today, in the spectrum of tasks solved by orbital spacecraft, there is a direction associated with an increase in both functional and thermal power radiated by the thermal control system into outer space. At thermal power more than 7 kW, there is a shortage of heat-radiating surfaces. The problem can be solved in three directions: increasing the temperature of the radiating surface; unfolding additional surfaces; utilization of thermal energy in the organic Rankine cycle. The key link in the implementation of the cycle is the modeling and design of a low-potential jet microturbine. When modeling the working process of such a turbine, a preliminary assessment of energy losses during the formation of a circumferential flow at the impeller inlet is necessary. One of the parameters determining part of the losses is the velocity coefficient φu . This work is devoted to the theoretical substantiation and method of experimental determination of the coefficient in the range of geometric and regime parameters of the tangential supply of a subsonic centripetal turbine.